Intervensi Kesiapsiagaan Psikolgis Bencana Banjir Pada Siswa-Siswi Di Lingkungan Sekolah - Jamali Jamali Jamali; Ahmad Guntur Alfianto; Rosly Zunaidi (Nursing News : Jurnal Ilmiah Keperawatan, 2022)
The pre-disaster phase must be strengthened with preparedness for students at school. At this time psychological disaster preparedness is also very important. This form of intervention focuses on preventing mental health problems before a disaster occurs. The purpose of this study was to identify the psychological flood preparedness intervention for students in the school environment. This research method uses a quantitative descriptive design with a survey approach. The population is high school students/equivalent with statified random sampling technique. the number of samples in this study were 80 respondents. The research site is in the city of Batu, East Java. The measuring instrument used in this study is the Psychological Preparedness for Disaster Threat Scale (PPDTS) questionnaire which has been translated into Indonesian. The results of psychological preparedness for flood disasters among students in the school environment with indicator 1 being in the medium category (56%), on indicator 2 with the medium category (71%), indicator 3 with the medium category (75%) and indicator 4 with the high category (48 %). The conclusion of the psychological preparedness of flood disasters in students in the school environment is the moderate category on the indicators of Knowledge and management of external environmental situations, emotional management and environmental response and social environmental management. As well as indicators with high categories are Anticipatory Coping with emotional responses